2018
DOI: 10.1155/2018/5206093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Functionalized Carbon Nanotubes and their Citric Acid Polymerization on Mesenchymal Stem Cells In Vitro

Abstract: The effects of acid-functionalized and polycitric acid- (PCA-) polymerized carbon nanotubes (CNTs) in contact with the extracellular membrane of mesenchymal stem cells (MSC), a genetically unmodified cell line with differentiation capability, was evaluated with different cellular parameters. The modified CNTs show differences in the analyzed biological behaviors, that is, intracellular incorporation, cell proliferation, apoptosis, and cytotoxicity as compared with those unpolymerized nanotubes. Due to the redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Another trend in the applications of CNTs is their combination with mesenchymal stem cells for tissue engineering and treatment of various disorders [152,153]. As well as for other types of stem cells, CNTs have been considered as a possible basis for growing and differentiation of mesenchymal stem cells.…”
Section: Carbon Nanotubes and Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another trend in the applications of CNTs is their combination with mesenchymal stem cells for tissue engineering and treatment of various disorders [152,153]. As well as for other types of stem cells, CNTs have been considered as a possible basis for growing and differentiation of mesenchymal stem cells.…”
Section: Carbon Nanotubes and Stem Cellsmentioning
confidence: 99%
“…It was shown that mesenchymal stem cells cultured on multi-walled CNTs possessed enhanced neural differentiation, indicating the importance of high electrical conductivity of the scaffolds for modulation of proliferation and differentiation of stem cells towards the normal neural tissue. Garnica-Gutiérrez et al studied the effects of acid-functionalized and polycitric acid-(PCA)-polymerized CNTs on mesenchymal stem cells in vitro, including intracellular incorporation, cell proliferation, apoptosis, and cytotoxicity [153]. It was found out that PCA-polymerized CNTs are less cytotoxic and are associated with less apoptotic cell death than the acid-functionalized ones.…”
Section: Carbon Nanotubes and Stem Cellsmentioning
confidence: 99%
“…Hence, they could be used as scaffolding materials to study the patterns of cellular growth such as adhesion and proliferation. 134 The mechanism of cytotoxicity on rat MSCs in vivo was dependent on mitochondrial and DNA damage, elevated oxidative stress, and damage to cell membranes. 135 The acid-functionalized SWCNTs can disrupt the tight junction barriers and cause cytotoxicity in Madin-Darby canine kidney II epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon nanotubes were widely investigated as contrast media for photoacoustic tomography and have been shown to enhance photoacoustic tomography imaging, especially in cancer treatments. The design and assessment of cyclic Gly/Arg/Asp (peptide)-single-wall carbon nanotube complex to target and detect tumours in vivo in a tumours model was one of the early examples of enhancements to photoacoustic tomography by using carbon nanotubes as contrast media [57].…”
Section: Deployment Of Carbon Nanotubes In Photoacoustic Imagingmentioning
confidence: 99%